Touristic’s Destination Brand Image: Proposition of a Measurement Scale for Rabat City (Morocco) - Abdellatif Elouali; Smail Hafidi Alaoui; Noura Ettahir; Abderrazzak Khohmimidi; Nadia Motii; Keltoum Rahali; Mustapha Kouzer (Advances in Science, Technology and Engineering Systems Journal, 2020)
The objective of this article is to highlight the existing relationship between the tourist’s destination brand image of the city of Rabat (Morocco) and its choice by foreign tourists to be visited once again. We suggest a reliable measurement scale able to measure the dimensions and associations of the brand image most memorized by tourists, so as to further attract the researchers and stakeholders curiosity in the tourism sector which face, every day, new challenges of attractiveness and sustainability of tourist destinations in the new Moroccan regionalization context. The survey is carried out on a sample of 454 foreign tourists in the city of Rabat because of the importance that this city requires in terms of overnight stays, that is to say nearly one million in 2018 according to the statistics of the Moroccan Tourism Observatory. The results obtained from the survey show that the functional and abstract associations jointly constitute the brand image of the city of Rabat in the foreign tourist’s memory and that the abstract associations are more significant in the destination’s choice.
Keywords: Brand Image; Touristic destination; Measurement scale; Morocco